A composite chemical fiber and preparation method thereof

By surface activation and epoxy resin coating on the inorganic reinforcement material, and combining with LDPE resin with granulation and crosslinking agent, the problem of existing anti-cut fiber inorganic particles is solved, and the cutting resistance and service life of the fiber is significantly improved.

CN115928235BActive Publication Date: 2025-03-25SHANDONG XINGYU CHENGYANG NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211718731.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-03-25
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

During the use of existing anti-cut fibers, inorganic reinforced particles are prone to fall off, resulting in a degradation of anti-cutting performance, and the fiber feels hard and lacks operating sensitivity.

Method used

By surface activation treatment and epoxy resin coating on the inorganic reinforcement material powder, the stability and binding force of the inorganic powder in the fiber matrix are ensured, and the use of LDPE resin blended granulation and crosslinking agents can improve the cutting resistance level and service life of the fiber.

Benefits of technology

It significantly improves the cutting resistance and service life of the fiber, avoids the problems of inorganic particles falling off and fiber breakage, and improves the mechanical properties of the fiber and the stability and comfort of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004028120830000111
    Figure BDA0004028120830000111
  • Figure BDA0004028120830000121
    Figure BDA0004028120830000121
Patent Text Reader

Abstract

The present invention relates to a composite chemical fiber and a preparation method thereof. The chemical fiber is acrylic fiber, nylon or polyester. The preparation method is as follows: firstly, surface activation treatment is performed on inorganic reinforcement particles to increase the oxygen-containing groups on the surface of the inorganic reinforcement particles and provide more sites for connection with a coupling agent, and then the inorganic reinforcement particles coated with epoxy resin are coated with epoxy resin, and then the inorganic reinforcement particles coated with epoxy resin are obtained by blending and granulating with a low melting point and low viscosity LDPE resin to obtain a cut-resistant LDPE masterbatch. Finally, the cut-resistant LDPE masterbatch and slices of acrylic fiber, nylon or polyester and a crosslinking agent are melt-spun by a screw extruder and a spinning assembly to obtain a cut-resistant composite chemical fiber. The method of the present invention can greatly improve the cutting resistance and durability of acrylic fiber, nylon or polyester chemical fiber, and avoid the wear of spinning equipment and weaving equipment due to the precipitation of inorganic particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemical fibers, and in particular to a composite chemical fiber and a preparation method thereof. Background Art

[0002] Anti-cut protective equipment includes anti-cut clothing, anti-cut gloves, anti-cut wrist guards, anti-cut leg guards, etc. Many anti-cut protective equipment on the market mainly include the following three forms: (1): Fabrics are obtained by blending cut-resistant wires such as stainless steel wire / glass fiber with chemical fibers such as polyester and acrylic fiber or cotton fiber, bamboo charcoal fiber, etc. This type of fabric is prone to revealing broken ends of steel wire / glass fiber during long-term use and friction, causing discomfort to the skin. (2): Cut-resistant wires such as stainless steel / glass fiber are used as core wires or intermediate yarns, and yarn coating technology is used on the outside, and chemical fibers such as acrylic fiber or cotton fiber, bamboo charcoal fiber are used as outer yarns for coating to obtain coated yarns. Compared with the first type, the use of these coated yarns to prepare fabrics can avoid direct contact between steel wire / glass fiber and skin, but with the increase of use, the broken ends of steel wire / glass fiber will be exposed, causing skin discomfort. In addition, due to the multi-layer twisting, the cost of this coated yarn is not only high, but also the formed coated yarn is thicker and harder. The fabric prepared after weaving is also harder, and very thin fabrics cannot be made. If used to make gloves, the gloves are stiff and the hand operation sensitivity is not enough after wearing. (3): Some cut-resistant inorganic powders or short fibers are added to the spinning solution during the spinning process, and the cut-resistant fibers are spun. For example, emulsified inorganic cut-resistant powders are added to the spinning solution of ultra-high molecular weight polyethylene fibers, and the mixture is extruded by an extruder, cooled in a coagulation bath, dried, and multi-stage hot drawing to obtain ultra-high cut-resistant ultra-high molecular weight polyethylene fibers. This fiber not only has strong cut resistance, but also because the inorganic powder and other materials are wrapped inside the fiber matrix, there is no problem of the end being exposed and piercing the skin, and the comfort is good. However, compared with other chemical fibers such as acrylic fibers, high molecular weight polyethylene fibers have poor spinnability, comfort, colorability, and wettability. They are not comfortable enough for making protective products such as cut-resistant gloves, and their application occasions are limited. Therefore, some people in the industry have proposed to prepare PET (polyester), acrylic, and nylon cut-resistant fibers by adding some inorganic reinforcing material powders / short fibers to PET (polyester), acrylic, and nylon fibers to obtain cut-resistant fibers.

[0003] For example, although the publication numbers CN114941183A and CN113897696 A add a certain proportion of anti-cutting functional masterbatch during the melt spinning process, the anti-cutting masterbatch is 10-15 parts by mass of functional inorganic powder, 1-3 parts by mass of dispersant, 0.25-0.50 parts by mass of coupling agent and 81-88 parts by mass of polyamide 6 slices, crushed and ground, and premixed in a high-speed mixer to obtain a mixed powder, which is vacuum dried to constant weight, melt extruded in an extruder, and water-cooled and granulated. Although this solution improves the anti-cutting performance of the fiber, it does not perform surface treatment on the inorganic ions. During the processing of the fiber, a large amount of inorganic particle powder will be scraped out during hooking and winding, which will scratch and wear the equipment while reducing the anti-cutting performance of the polyester fiber. As the use time becomes longer and inorganic particles continue to precipitate from the fiber, the anti-cutting performance of this fiber decreases rapidly. At the same time, inorganic particles are easily precipitated from the fibers during the spinning process, causing fiber breakage and forming hairy fibers, which affects the fiber quality and production stability, reduces the manufacturing rate, and greatly increases the production cost. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a composite chemical fiber and a preparation method thereof, which are used to prepare cut-resistant acrylic fiber, nylon and polyester; mainly by surface treating the inorganic reinforcing material powder so that the inorganic powder can be more firmly retained in the fiber matrix without damaging the strength of the inorganic powder, thereby achieving the purpose of enhancing the cut resistance level and service life of the chemical fiber.

[0006] (II) Technical solution

[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0008] In a first aspect, the present invention provides a method for preparing a composite chemical fiber, wherein the chemical fiber is acrylic fiber, nylon fiber or polyester fiber, and the preparation method comprises:

[0009] S1. performing surface activation treatment on the inorganic reinforcing particles, wherein the surface activation treatment includes surface oxidation treatment and coupling agent treatment. If oxygen-containing groups already exist on the surface of the inorganic reinforcing particles, the coupling agent treatment is directly performed;

[0010] S2, spraying the diluted epoxy resin glue onto the inorganic reinforcing particles, drying, crushing and grinding, and passing through a 200-1500 mesh sieve to obtain epoxy resin-coated inorganic reinforcing particles;

[0011] S3, sprinkle the inorganic reinforced particles with epoxy resin coated on the surface obtained in S2 into the LDPE resin which has been preheated to a molten state, stir evenly, cool and then transport to a screw granulator for extrusion granulation, cool and obtain a cut-resistant LDPE masterbatch;

[0012] S4, adding acrylic fiber, nylon or polyester slices, cut-resistant LDPE masterbatch and cross-linking agent into a mixing bin at a mass ratio of 100:8-25:2-6, and mixing and stirring in a high-speed mixer to obtain a mixture;

[0013] S5, adding the mixed material into a screw extruder for melt extrusion, filtering through a filter, extruding and spinning through the holes of a spinneret, and cooling by side blowing to obtain solidified filaments; and then oiling with an oiling roller, stretching with a hot roller, shaping, and winding to obtain a cut-resistant composite chemical fiber.

[0014] According to a preferred embodiment of the present invention, in S1, the surface oxidation treatment includes one or more of gas phase oxidation, liquid phase oxidation, catalytic oxidation, and plasma oxidation.

[0015] According to a preferred embodiment of the present invention, in S1, the inorganic reinforcing particles are one or more of silicon carbide powder, boron nitride powder, carbon fiber staple fibers, basalt staple fibers, carbon nanotubes, silicon dioxide, glass powder, etc.; and the diameter of the inorganic reinforcing particles is 0.1-100 μm.

[0016] The silicon carbide powder comes from waste silicon carbide refractory bricks. At this time, a layer of SiO2 film is formed on the surface of the silicon carbide powder, which can avoid oxidation treatment.

[0017] According to a preferred embodiment of the present invention, in S1, the coupling agent is at least one of the silane coupling agents A171, KH550, KH580, KH590, KH792, and DL602.

[0018] Preferably, the coupling agent treatment method is: immersing the inorganic reinforcing particles that have undergone surface oxidation treatment into a coupling agent treatment solution and leaving it to soak at room temperature for 5-24 hours, then taking it out and drying it; the coupling agent treatment solution is prepared from 2-5 parts by mass of a silane coupling agent, 20-40 parts by mass of ethanol, and 1-2 parts by mass of water, and the pH is adjusted to 8-9 with aqueous ammonia.

[0019] According to a preferred embodiment of the present invention, in S2, the diluted epoxy resin glue is prepared by using an epoxy resin diluent to maintain the viscosity of the epoxy resin at 0.3-0.7 Pa.s (700 cP (centipoise)) (25°C); the method of spraying the diluted epoxy resin glue onto the inorganic reinforcing particles is as follows: while the inorganic reinforcing particles are kept in a fluidized state, the epoxy resin glue is sprayed onto the surface of the inorganic reinforcing particles, and dried and solidified during the falling process; and the epoxy resin diluent is recovered at the same time.

[0020] According to a preferred embodiment of the present invention, in S3, the mixing mass ratio of the inorganic reinforcing particles coated with epoxy resin and the LDPE resin is 25-40:80-100; the LDPE is a low melting point and low viscosity resin with a melting point of 110-115°C and a viscosity of 150mPa.s-500mPa.s at 125°C.

[0021] According to a preferred embodiment of the present invention, in S4, the crosslinking agent is one or more of tricyclohexylphosphine, binaphthol, and bis(diphenylphosphino)ferrocene. The crosslinking agent material involved in the bonding will at least provide an electron to form a covalent bond or complex coordination, increase the compatibility of the slices with the LDPE masterbatch, reduce the internal energy between molecules, form a synergistic effect, thereby improving the mechanical properties and tensile strength of the chemical fiber, reducing the occurrence of breakage during the spinning process, avoiding the formation of hair, and enhancing the mechanical strength, product quality and stability of the cut-resistant composite chemical fiber.

[0022] According to a preferred embodiment of the present invention, S4 also includes 1-2 parts by mass of an antioxidant, wherein the antioxidant is one or more of antioxidant 1010, antioxidant 168, antioxidant 1076, and antioxidant 164, thereby enhancing the aging resistance and durability of the cut-resistant composite chemical fiber, making the chemical fiber matrix (acrylic, polyester or nylon) itself less likely to break and exerting a cut-resistant effect for a long time.

[0023] According to a preferred embodiment of the present invention, in S5: the blowing cooling conditions are: the cooling air temperature is 20-25°C, the humidity is 65-70%, and the wind speed is 0.5-0.7m / s; the setting temperature of polyester or nylon is 160-180°C, the setting temperature of acrylic is 220-250°C, and the winding speed is 4500-4800m / min.

[0024] In a second aspect, the present invention provides a cut-resistant composite chemical fiber, wherein the chemical fiber is acrylic fiber, nylon fiber or polyester fiber, and is prepared by the preparation method of any of the above embodiments.

[0025] (III) Beneficial effects

[0026] The beneficial effects of the present invention are:

[0027] The present invention performs surface activation treatment on inorganic reinforcement particles to increase oxygen-containing groups on the surface of the inorganic reinforcement particles, provide more sites for connection with a coupling agent, and then use epoxy resin glue to coat the whole, and then dry, crush, grind, and sieve to obtain inorganic reinforcement particles coated with epoxy resin, and blend and granulate the inorganic reinforcement particles coated with epoxy resin with low melting point and low viscosity LDPE resin to obtain cut-resistant LDPE masterbatch. Finally, the cut-resistant LDPE masterbatch and acrylic fiber, nylon or polyester slices and a crosslinking agent are melt-spun using a screw extruder and a spinning assembly to obtain a cut-resistant composite chemical fiber.

[0028] Compared with the method of chemical etching or laser etching to form obvious rough lines on the surface of inorganic reinforcing particles or staple fibers, the present invention can maximize the cutting resistance and hardness of inorganic reinforcing particles. The coupling agent can be connected to the surface of inorganic reinforcing particles or staple fibers by coupling agent treatment, and then the epoxy resin glue is used for overall coating. The film-forming property and strong adhesion of the epoxy resin glue are used to make the entire outer surface of the inorganic reinforcing particles have the properties of organic resin, and the cracks of the inorganic particles are repaired to enhance the mechanical strength, cutting resistance and toughness of the inorganic particles themselves. After coating, the particles are crushed and ground, and only 200-1500 mesh particle sizes are retained by screening (other particle sizes are eliminated), so as to achieve the effect of tidying the particle size (whole particle effect), reduce the angular coefficient of the inorganic reinforcing particles, and make the inorganic reinforcing particles used to prepare chemical fibers have a relatively uniform particle size. Furthermore, the comprehensive wrapping of epoxy resin makes the inorganic particles have excellent adhesion and wettability with the resin, and can be evenly dispersed in the LDPE resin. In the process of melt extrusion spinning in the screw extruder, the epoxy resin is close to the melting point and produces strong adhesiveness, so that the inorganic reinforcing particles are tightly fixed in the chemical fiber matrix such as acrylic, nylon or polyester. At the same time, under the action of the cross-linking agent, it can produce covalent cross-linking with PET (acrylic or nylon), which further enhances the bonding degree between the inorganic reinforcing particles and the fiber, and avoids the problem of the inorganic reinforcing particles being scraped out when the fiber is hooked and wound. The trial production experiment has proved that if the inorganic reinforcing particles are not surface treated or the cross-linking agent is not added during spinning, the cutting resistance of the final chemical fiber will decrease, and after repeated winding and bending, the performance of the chemical fiber will decrease significantly. This is caused by the insufficient bonding between the inorganic reinforcing particles and the fiber. When using this kind of chemical fiber fabric to make anti-cut gloves and other items, powder will continue to precipitate during the working process, and the product's cut resistance level will drop rapidly, polluting the working environment and causing serious wear and tear on equipment parts.

[0029] The low melting point and low viscosity LDPE resin is blended and granulated with the inorganic reinforcement particles coated with epoxy resin. Since LDPE has a low melting point and low viscosity, the inorganic reinforcement particles are sprinkled into the LDPE resin that has been preheated into a liquid. After stirring, a very uniformly dispersed mixture can be obtained. Compared with the prior art, the solid-phase LDPE resin and the inorganic powder are directly mixed and granulated, which can completely avoid the problem of powder sinking and stratification and inability to achieve uniform mixing due to the small inorganic powder particles and large LDPE slice particles, thereby affecting the dispersion uniformity of the inorganic particles in the LDPE masterbatch and the cutting resistance of the chemical fiber product. DETAILED DESCRIPTION

[0030] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with specific implementation methods.

[0031] Example 1

[0032] This embodiment is a method for preparing a highly cut-resistant polyester yarn, the preparation method comprising:

[0033] (1) Use waste silicon carbide refractory bricks and grind them into silicon carbide powder of 0.1-100 μm. The silicon carbide surface of the waste silicon carbide refractory bricks has a SiO2 layer. Prepare a coupling agent treatment liquid, which is prepared from 4 parts by mass of silane coupling agent A171, 25 parts by mass of ethanol, and 1 part by mass of water, and adjust the pH to 8.5 with ammonia water. Soak the silicon carbide powder in the coupling agent treatment liquid, let it stand at room temperature for 8 hours, take it out, and dry it.

[0034] (2) While keeping the silicon carbide powder in a fluidized state, spray a diluted epoxy resin glue (aliphatic epoxy resin) with a viscosity of 0.5 Pa.s onto the powder surface, dry and solidify, crush and grind, retain part of the silicon carbide particles passing through a 200-1000 mesh sieve, recycle the fine particles, sprinkle glue for reuse, and further grind the coarse particles.

[0035] (3) Use LDPE resin (150mPa.s, 125°C) with a melting point of 110-115°C, preheat until completely melted, then sprinkle the silicon carbide particles coated with epoxy resin obtained in step (2) into the LDPE resin melt, and stir at a stirring speed of 2000-2500rpm in a stirring tank for 20 minutes. The mass ratio of silicon carbide particles to LDPE resin is 25:80. After stirring evenly, cool to 50°C, and then transport to a screw granulator for extrusion granulation, cool, and obtain a cut-resistant LDPE masterbatch.

[0036] (4) After the polyester chips are deironed, pre-crystallized, and dried, they are added into a mixing bin with cut-resistant LDPE masterbatch and a cross-linking agent, tricyclohexylphosphine, at a mass ratio of 100:20:4, for dry mixing to obtain a mixture.

[0037] (5) Add the mixed material into a screw extruder for melt extrusion, filter it through a filter, extrude it through the spinneret holes, and cool it by side blowing to obtain solidified filaments; then oil it with an oiling roller, stretch it with a hot roller, shape it, and wind it up to obtain a high-cutting-resistant polyester filament. The blowing cooling conditions are: cooling air temperature of 20-25°C, humidity of 65-70%, wind speed of 0.5-0.7m / s; shaping temperature of 165°C, and winding speed of 4500m / min.

[0038] Example 2

[0039] This embodiment is a method for preparing a highly cut-resistant nylon yarn, the preparation method comprising:

[0040] (1) Use waste glass and grind it into glass powder of 0.1-100 μm. Prepare a coupling agent treatment liquid, which is prepared by 5 parts by mass of silane coupling agent KH550, 30 parts by mass of ethanol, and 1.5 parts by mass of water, and adjust the pH to 8.5 with ammonia water. Soak the glass powder in the coupling agent treatment liquid and leave it to stand at room temperature for 8 hours, then take it out and dry it.

[0041] (2) While keeping the glass powder in a fluidized state, spray a diluted epoxy resin glue (aliphatic epoxy resin) with a viscosity of 0.5 Pa.s onto its surface, dry and solidify it, crush and grind it, retain some glass particles passing through a 200-1200 mesh sieve, recycle the fine particles, sprinkle glue for reuse, and further grind the coarse particles.

[0042] (3) Using LDPE resin (150 mPa.s, 125°C) with a melting point of 110-115°C, preheat it until it is completely melted, then sprinkle the glass particles coated with epoxy resin obtained in step (2) into the LDPE resin melt, and stir it in a stirring tank at a stirring speed of 2000-2500 rpm for 20 minutes. The mass ratio of glass particles to LDPE resin is 30:100. After stirring evenly, cool to 50°C, and then transport it to a screw granulator for extrusion granulation, cool it, and obtain a cut-resistant LDPE masterbatch.

[0043] (4) After the nylon chips are deironed, pre-crystallized, and dried, they are added into a mixing bin with the cut-resistant LDPE masterbatch and the cross-linking agent binaphthol at a mass ratio of 100:16:5 to obtain a mixture.

[0044] (5) Add the mixed material into a screw extruder for melt extrusion, filter it through a filter, and then extrude it through the spinneret holes for spinning. Then, cool it with side air to obtain solidified filaments. Then, oil it with an oiling roller, stretch it with a hot roller, set it, and wind it up to obtain high-cut-resistant nylon yarn. The conditions for air cooling are: cooling air temperature of 20-25°C, humidity of 65-70%, wind speed of 0.5-0.7m / s; setting temperature of 180°C, and winding speed of 4500m / min.

[0045] Example 3

[0046] This embodiment is a method for preparing a highly cut-resistant acrylic yarn, the preparation method comprising:

[0047] (1) Use carbon fiber staple fibers with a length of 0.1-100 μm, soak them in concentrated nitric acid at 50-60°C for 6 hours, take them out and dry them. Prepare a coupling agent treatment solution, which is prepared from 4 parts by mass of silane coupling agent DL602, 30 parts by mass of ethanol, and 1.5 parts by mass of water, and adjust the pH to 8.5 with ammonia water. Soak the carbon fiber staple fibers in the coupling agent treatment solution, let it stand at room temperature for 8 hours, take it out and dry it.

[0048] (2) While keeping the carbon fiber staple fibers in a fluidized state, spray a diluted epoxy resin glue (aliphatic epoxy resin) with a viscosity of 0.4 Pa.s on its surface, dry and solidify, crush and grind, retain part of the carbon fiber staple fibers that pass through a 300-1250 mesh sieve, recycle the fine particles, sprinkle glue for reuse, and further grind the coarse particles.

[0049] (3) Use LDPE resin (150mPa.s, 125°C) with a melting point of 110-115°C, preheat until completely melted, then sprinkle the glass particles coated with epoxy resin obtained in step (2) into the LDPE resin melt, and stir at a stirring speed of 3000rpm in a stirring tank for 20 minutes. The mass ratio of glass particles to LDPE resin is 30:90. After stirring evenly, cool to 50°C, and then transport to a screw granulator for extrusion granulation, cool, and obtain a cut-resistant LDPE masterbatch.

[0050] (4) After the acrylic fiber chips are deironed, pre-crystallized, and dried, they are added into a mixing bin for dry mixing with the cut-resistant LDPE masterbatch, the crosslinking agent bis(diphenylphosphino)ferrocene, and the antioxidant 1010 at a mass ratio of 100:15:4:1 to obtain a mixture.

[0051] (5) Add the mixed material into a screw extruder for melt extrusion, filter it through a filter, and then extrude it through the spinneret holes for spinning, and cool it by side blowing to obtain solidified filaments; then oil it with an oiling roller, stretch it with a hot roller, set it, and wind it up to obtain a high-cut-resistant acrylic fiber. The conditions for blowing cooling are: cooling air temperature of 20-25°C, humidity of 65-70%, wind speed of 0.5-0.7m / s; setting temperature of 240°C, and winding speed of 4800m / min.

[0052] Example 4

[0053] The method for preparing the highly cut-resistant polyester yarn in this embodiment is different from that in Embodiment 1 only in that the silicon carbide powder in step (1) is replaced with an equal amount of silicon dioxide powder. The remaining processing conditions and methods are the same as those in Embodiment 1.

[0054] Example 5

[0055] The method for preparing the highly cut-resistant polyester yarn of this embodiment is different from that of embodiment 1 only in that the silicon carbide powder in step (1) is replaced with an equal amount of boron nitride powder, and the surface of the boron nitride is oxidized by plasma oxidation technology. The remaining processing conditions and methods are the same as those of embodiment 1.

[0056] Example 6

[0057] The method for preparing the highly cut-resistant polyester yarn in this embodiment is different from that in Embodiment 1 only in that 1 part by mass of antioxidant 168 is further added in step (4). The rest of the processing conditions and methods are the same as those in Embodiment 1.

[0058] Example 7

[0059] The method for preparing high-cut-resistant polyester yarn in this embodiment is different from that in Example 1 only in that in step (1), the silicon carbide powder is immersed in the coupling agent treatment liquid and left to stand at room temperature for 24 hours before being taken out and dried. The remaining treatment conditions and methods are the same as those in Example 1.

[0060] Example 8

[0061] The method for preparing the high-cut-resistant nylon yarn in this embodiment is different from that in Embodiment 2 only in that the glass powder in step (1) is replaced with an equal amount of basalt particles. The rest of the processing conditions and methods refer to those in Embodiment 2.

[0062] Example 9

[0063] The method for preparing the high-cut-resistant nylon yarn of this embodiment is different from that of Embodiment 2 only in that the glass powder in step (1) is replaced with an equal amount of carbon fiber staple fibers, and the fibers are immersed in concentrated nitric acid at 50-60° C. for 6 h, and then taken out and dried. The remaining treatment conditions and methods are the same as those of Embodiment 2.

[0064] Example 10

[0065] The method for preparing the highly cut-resistant nylon yarn of this embodiment is different from that of Embodiment 2 only in that in step (3), the glass particles and LDPE resin are mixed in a mass ratio of 30:95. The rest of the processing conditions and methods are the same as those of Embodiment 2.

[0066] Embodiment 11

[0067] The method for preparing highly cut-resistant acrylic yarn in this embodiment is different from that in Example 3 only in that the carbon fiber staple fibers in step (1) are replaced with carbon nanotubes and carbon fiber staple fibers mixed in a mass ratio of 1:1, and are immersed in concentrated nitric acid at 50-60° C. for 6 h. The remaining treatment conditions and methods are the same as those in Example 3.

[0068] Example 12

[0069] The method for preparing highly cut-resistant acrylic yarn in this embodiment is different from that in Example 3 only in that an epoxy resin glue (glycidylamine epoxy resin) with a diluted viscosity of 0.7 Pa.s is used in step (2), dried and solidified, crushed and ground, and part of the carbon fiber staple fibers passing through the 800-1500 mesh sieve are retained, the over-fine particles are recovered and reused by spraying glue, and the over-coarse particles are further ground. The remaining processing conditions and methods refer to Example 3.

[0070] Example 13

[0071] The method for preparing the highly cut-resistant acrylic yarn of this embodiment is different from that of Embodiment 3 only in that, in step (3), LDPE resin (375 mPa.s, 125°C) with a melting point of 110-115°C is used, which is preheated to be completely melted, and then the glass particles coated with epoxy resin obtained in step (2) are sprinkled into the LDPE resin melt, and stirred at a stirring speed of 3000 rpm in a stirring tank for 20 minutes. The remaining processing conditions and methods are as in Embodiment 3.

[0072] Based on the scheme of the present invention, by changing some conditions, the following implementation control example is obtained.

[0073] Comparative Example 1

[0074] This comparative example is a method for preparing a highly cut-resistant polyester yarn, and the difference between the preparation method and Example 1 is that the treatment in step (2) is not performed. The remaining treatment conditions and methods are the same as those in Example 1.

[0075] Comparative Example 2

[0076] This comparative example is a method for preparing a highly cut-resistant polyester yarn. The difference between the preparation method and Example 1 is that, when preparing the masterbatch in step (3), the PET resin and the silicon carbide particles prepared in step (2) are solid-solid dry mixed in a mixing bin and then sent to a screw granulator for extrusion granulation. The remaining processing conditions and methods are the same as those in Example 1.

[0077] Comparative Example 3

[0078] This comparative example is a method for preparing a highly cut-resistant polyester yarn, and the difference between the preparation method and Example 1 is that no coupling agent treatment liquid immersion treatment is performed in step (1). The remaining treatment conditions and methods refer to Example 1.

[0079] Comparative Example 4

[0080] This comparative example is a method for preparing a highly cut-resistant polyester yarn. The difference between the preparation method and Example 1 is that, in step (1), before the immersion in the coupling agent treatment solution, the silicon carbide is etched by immersing in 15% NaOH at 40°C for 2 hours and then taken out and dried. The remaining treatment conditions and methods refer to Example 1.

[0081] Comparative Example 5

[0082] This comparative example is a method for preparing a highly cut-resistant polyester yarn, and the difference between the preparation method and Example 1 is that no crosslinking agent is added when preparing the mixed material in step (4). The remaining processing conditions and methods are the same as those in Example 1.

[0083] The cut-resistant chemical fiber yarns of Examples 1-12 and Comparative Examples 1-5 were made into 200D, 20F yarns, which were then knitted into 13-gauge glove blanks. After being worn by workers in the same position and performing the same operation for 1 day and 22 days, the cut resistance (cutting index) of the gloves was tested respectively.

[0084] The test method is: EN388-2003. European standard for gloves for protection against mechanical damage. This test uses the Couptest cutting tester. Under fixed load, a circular blade is used to roll back and forth on the sample (3 random positions on the glove blank) until it is cut. Cotton canvas is used as the reference material for verifying the sharpness of the blade. The reference material and the test sample are cut alternately until five test results are obtained. The cut resistance performance is the ratio of the number of cycles required to cut the test material to the reference material, that is, the cutting index.

[0085] The test results are shown in the following table:

[0086]

[0087]

[0088] It can be seen from Examples 1, 4-7 and Comparative Examples 1-5 that the cut-resistant index of the cut-resistant polyester fiber of the present invention is higher than that of Comparative Examples 1-5, and the cut-resistant grade is between A4-5. Although it is not as good as the cut-resistant strength of ultra-high molecular weight polyethylene modified by inorganic reinforcing materials, it also meets the requirements of labor protection. Most importantly, cut-resistant polyester, nylon or acrylic fiber has lower surface energy than ultra-high molecular weight polyethylene, good colorability, and the woven fabric is light and comfortable to wear, and has high operational sensitivity.

[0089] Comparing Example 1 with Control Example 1, it can be seen that the anti-cutting index of the polyester glove blank prepared in Control Example 1, which has not been repaired with epoxy resin glue to repair the cracked inorganic particle pattern, granulate and fully coated, is significantly lower than that in Example 1, especially after 22 days of wearing and working, the index is significantly lower than that just completed, and burrs and scratches appear on the surface of the glove blank. Control Example 3 has not been treated with coupling agent treatment liquid, and the product has similar problems, but the situation is better than that of Control Example 1. In Control Example 2, PET is used in the preparation of cut-resistant masterbatch. This resin not only has high viscosity but also adopts solid-solid mixing, resulting in obvious stratification of silicon carbide particles and PET slice particles, and finally making the silicon carbide particles unevenly distributed in the cut-resistant polyester fiber. Therefore, when testing the anti-cutting index, the highest and lowest values ​​of the test results are quite different, showing that the anti-cutting performance is very uneven. In Comparative Example 4, several pits were formed on the surface of silicon carbide by etching to increase the roughness and specific surface area. Although the cut resistance index of the glove blank did not decrease significantly with the use time (indicating that the silicon carbide fiber was firmly embedded in the polyester), the cut resistance performance was poorer than that of Examples 1 and 4-7. This was mainly because the etching operation reduced the hardness and strength of the silicon carbide particles themselves, resulting in insufficient cut resistance of the polyester. In Comparative Example 5, no crosslinking agent was added during the spinning process, and the cut resistance index of the glove blank also decreased significantly compared with Examples 1 and 4-7.

[0090] Compared with Examples 1, 2, and 3, the anti-cutting index of the polyester chemical fiber glove blank is higher than that of nylon and acrylic. When the chemical fiber matrix is ​​the same, the anti-cutting index is positively correlated with the Mohs hardness of the inorganic reinforcing particles used.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a composite chemical fiber, wherein the chemical fiber is acrylic fiber, nylon fiber or polyester fiber, characterized in that: The preparation method comprises: S1. performing surface activation treatment on the inorganic reinforcing particles, wherein the surface activation treatment includes surface oxidation treatment and coupling agent treatment. If oxygen-containing groups already exist on the surface of the inorganic reinforcing particles, the coupling agent treatment is directly performed; S2, spraying the diluted epoxy resin glue onto the inorganic reinforcing particles, drying, crushing, grinding, and passing through a 200-1500 mesh sieve to obtain epoxy resin-coated inorganic reinforcing particles; S3, sprinkle the inorganic reinforced particles with epoxy resin coated on the surface obtained in S2 into the LDPE resin which has been preheated to a molten state, stir evenly, cool and then transport to a screw granulator for extrusion granulation, cool and obtain a cut-resistant LDPE masterbatch; S4, adding acrylic fiber, nylon or polyester slices, cut-resistant LDPE masterbatch and cross-linking agent into a mixing bin at a mass ratio of 100:8-25:2-6, and mixing and stirring in a high-speed mixer to obtain a mixture; S5, adding the mixed material into a screw extruder for melt extrusion, filtering through a filter, extruding and spinning through the holes of a spinneret, and cooling by side blowing to obtain solidified filaments; and then oiling with an oiling roller, stretching with a hot roller, shaping, and winding to obtain a cut-resistant composite chemical fiber.

2. The preparation method according to claim 1, characterized in that: In S1, the surface oxidation treatment includes one or more of gas phase oxidation, liquid phase oxidation, catalytic oxidation and plasma oxidation.

3. The preparation method according to claim 1, characterized in that: In S1, the inorganic reinforcing particles are one or more of silicon carbide powder, boron nitride powder, carbon fiber staple fibers, basalt staple fibers, carbon nanotubes, silicon dioxide and glass powder; and the particle size of the inorganic reinforcing particles is 0.1-100 μm.

4. The preparation method according to claim 1, characterized in that: In S1, the coupling agent is at least one of silane coupling agents A171, KH550, KH580, KH590, KH792 and DL602; the coupling agent treatment method is: immersing the inorganic reinforcing particles that have undergone surface oxidation treatment into a coupling agent treatment liquid, leaving them to soak for 5-24 hours at room temperature, taking them out, and drying them; the coupling agent treatment liquid is prepared from 2-5 parts by mass of silane coupling agent, 20-40 parts by mass of ethanol, and 1-2 parts by mass of water, and the pH is adjusted to 8-9 with ammonia water.

5. The preparation method according to claim 1, characterized in that: In S2, the diluted epoxy resin glue is prepared by using an epoxy resin diluent to keep the viscosity of the epoxy resin at 0.3-0.7 Pa.s; the method for spraying the diluted epoxy resin glue onto the inorganic reinforcing particles is as follows: while the inorganic reinforcing particles are kept in a fluidized state, the epoxy resin glue is sprayed onto the surface of the inorganic reinforcing particles, and the epoxy resin glue is dried and solidified during the falling process; and the epoxy resin diluent is recovered at the same time.

6. The preparation method according to claim 1, characterized in that: In S3, the mixing mass ratio of inorganic reinforcing particles coated with epoxy resin and LDPE resin is 25-40:80-100; the LDPE is a low melting point and low viscosity resin with a melting point of 110-115°C and a viscosity of 150mPa.s-500mPa.s at 125°C.

7. The preparation method according to claim 1, characterized in that: In S4, the cross-linking agent is one or more of tricyclohexylphosphine, binaphthol and bis(diphenylphosphino)ferrocene.

8. The preparation method according to claim 1, characterized in that: In S4, the mixture further includes 1-2 parts by mass of an antioxidant, and the antioxidant is one or more of antioxidant 1010, antioxidant 168, antioxidant 1076 and antioxidant 164.

9. The preparation method according to claim 1, characterized in that: In S5: the blowing cooling conditions are: cooling air temperature is 20-25°C, humidity is 65-70%, wind speed is 0.5-0.7m / s; the setting temperature of polyester or nylon is 160-180°C, the setting temperature of acrylic is 220-250°C, and the winding speed is 4500-4800m / min.

10. A composite chemical fiber, wherein the chemical fiber is acrylic fiber, nylon fiber or polyester fiber, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Anti-cutting modified regenerated polyester fiber as well as preparation method and textile product thereof

    CN114941183A

  • High-wear-resistance crosslinked polyethylene material and preparation method thereof

    CN111607152A

  • Anti-cutting polyamide 6 fiber preparation method

    CN113897696A